AN ANALYSIS OF SOCIAL VALUES IN THE NOVEL “GROUND ZERO “BY AGUSTINUS WIBOWO - Umar, Umar (Yayasan Akrab Pekanbaru, 2018)
In this research the writer seen the social phenomenon that shows in the novel Ground Zero by Agustinus Wibowo. The purpose of this study is to describe the social value in the novel Ground Zero by Agustinus Wibowo. This research using the content analysis approach is a research technique to make replicable with regard to its context. The research method used descriptive qualitative method to presents the data decomposed based on objective facts in accordance with the data contained in the social value in the novel Ground Zero by Agustinus Wibowo. The data in this study are the words or sentence contained in the novel text of Ground Zero. Source of data in this research is novel Ground Zero by Agustinus Wibowo Published by PT. Gramedia Pustaka Utama in 2013 with 556 pages. The technique of data collection used of close reading, noting and quoting. The results of this study found types of social values that are generally divided into three that is; value of affection, value of responsibility, and the value of harmony of life. Specifically the types of social value is divided into fourteen (14) social value they are;The value of affection consists of love or affection, devotion, mutual help, kinship, caring and respect to parents. The social value of responsibility consists of obligations, discipline, keeping promises, independence and trust. Furthermore, the value of harmony of life consists of cooperation, togetherness and adherence to custom. The types of social values mentioned above the most dominant value in the novel is the social value of caring. Keywords: Novel, Social, Value.